Media coverage of the 20th African Men's Handball Championship held in Morocco, as reflected in the print sports press: An analytical study of the Al-Shorouk Al-Yawmi newspaper. - saleh ouaffi, nabil; mouafek, saleh; Laoucine, slimane (sports creativity, 2025)
The media plays a vital role in the socialization, normalization, and overall social development of the individual. Thanks to modern communication technologies, which have brought the world closer together, each part is now influenced by and responds to the others. This interconnectedness can only be countered through the media.